Cover, Content, and Editorial Note from Borneo J Pharm Vol. 5 No. 2 May 2022 - Chief Editor of Borneo J Pharm (Borneo Journal of Pharmacy, 2022)
Assalamu’alaikum Wr. Wb. Alhamdulillahirabbil ‘alamin. The next edition of the Borneo Journal of Pharmacy (Borneo J Pharm) has been published in May 2022. This edition contains ten articles consisting of Pharmacology-Toxicology, Pharmacognosy-Phytochemistry, Pharmaceutical, Microbiology Pharmacy, Natural Product Development, and Clinical-Community Pharmacy. This edition includes writings from four countries, including India, Indonesia, Nigeria, and Sri Lanka. The authors come from several institutions, including Universitas Pancasila, University of Jaffna, Universitas Muhammadiyah Prof. Dr. HAMKA, Universitas Setia Budi, Federal University Birnin Kebbi, Kano State Polytechnic, Universitas Muhammadiyah Palangkaraya, Prathima Institute of Medical Sciences, Bhaskar Pharmacy College, Ganapathy Degree College, Universitas Muhammadiyah Malang, Universitas Muhammadiyah Magelang, and Universitas Andalas. Editorial boards are fully aware that there is still room for improvement in this edition, hence with all humility, willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank all editors and reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope that all parties, especially the contributors, could re-participate for publication in the next edition in August 2022. Wassalamu’alaikum Wr. Wb.